Students' perceptions of the instructional quality of district hospital-based training - Shehla Jabbar Memon; Jakobus Murray Louw; Martin Bac; Jannie Hugo; Waqar-un Nisa Rauf; John Edward Sandars (AOSIS, 2016)
Background: An innovative, three-year training programme, the Bachelor of Clinical Medical Practice (BCMP), for mid-level medical healthcare workers was started in 2009 by the Department of Family Medicine, University of Pretoria. Aim: To measure the students' perceptions of the instructional quality of district hospitalbased training. Setting: Training of students took place at clinical learning centres in rural district hospitals in the Mpumalanga and Gauteng provinces. Methods: A survey using the MedEd IQ questionnaire was performed in 2010 and 2011 to measure BCMP second- and third-year students' perceptions of instructional quality of district hospital-based training. The MedEd IQ questionnaire is composed of four subscales: preceptor activities, learning opportunities, learner involvement and the learning environment. Composite scores of instructional quality were used to present results. Results: The preceptor activities, learning opportunities and the learning environment were considered by second- and third-year BCMP students to be of consistently high instructional quality. In the area of learner involvement, instructional quality increased significantly from second to third year. Conclusion: Overall, instructional quality of district hospital-based training was high for both second- and third-year BCMP students, and the instructional quality of learner involvement being significantly higher in third year students. The MedEd IQ tool was a useful tool for measuring instructional quality and to inform programme quality improvement. Keywords: clinical associates, evaluation of medical education, mid-level healthcare workers, rural learning centres, rural medical education, student satisfaction.